PROTOTIPE PENGONTROLAN PINTU GUNA MENGAMANKAN NASKAH SOAL UJIAN NASIONAL PADA SMA NEGERI 11 TANGERANG - Ferry Sudarto S.Kom; Eka Purwandari; Aldien Sora Andrea (CCIT Journal, 2018)
Research on "PROTOTYPE DOOR CONTROLLING TO SAVE NATIONAL EXAM SCRIPT AT 11 SENIOR HIGH SCHOOL TANGERANG" aims to provide security benefits in the national exam deception problems. This research was carried out by making a prototype in the form of a door with a security system using technologies of embedded systems. Namely to control a door through Android smartphone. This is because the security system is not running optimally so often lead to deception. Therefore, we need a system to facilitate and secure the national examination script . All this time during the security room to store national test script using only a padlock. This research will provide an overview of the complex mechanisms such as how a door will lock securely using an application on Android smarthphone as the key. The prototype uses a door control basic 4 android as an interface between users. By using Bluetooth as a sensor signal to the sender to call the personal computer (pc) database and added arduino uno as a DC motor controllers. Prototype controlling these doors can be a reference to the department in dealing with security issues manuscript national exam